Anti-neuroinflammatory Activity of Kamebakaurin From Isodon japonicus via Inhibition of c-Jun NH2-Terminal Kinase and p38 Mitogen-Activated Protein Kinase Pathway in Activated Microglial Cells - Byung-Wook Kim; Sushruta Koppula; In Su Kim; Hyung-Woo Lim; Sun-Min Hong; Sang-Don Han; Bang-Yeon Hwang; Dong-Kug Choi (Journal of Pharmacological Sciences, 2011)
Abstract.: Compelling evidence supports the notion that the majority of neurodegenerative diseases are associated with microglia-mediated neuroinflammation. Therefore, quelling of microglial activation may lead to neuronal cell survival. The present study investigated the effects of Kamebakaurin (KMBK), a kaurane diterpene isolated from Isodon japonicus HARA (Labiatae), on the production of pro-inflammatory mediators in lipopolysaccharide (LPS)-stimulated cytotoxicity in rat primary microglial cultures and the BV-2 cell line. KMBK significantly inhibited the LPS-induced production of nitric oxide (NO) in a concentration-dependent fashion in activated microglial cells. The mRNA and protein levels of inducible nitric oxide synthase (iNOS) and cyclooxycenase-2 (COX-2) were also decreased dose-dependently. Furthermore KMBK inhibited the JNK and p38 mitogen-activated protein kinases (MAPKs) in LPS-stimulated BV-2 microglial cells. Considering the results obtained, the present study authenticated the potential benefits of KMBK as a therapeutic target in ameliorating microglia-mediated neuroinflammatory diseases. Keywords:: microglia, neuroinflammation, nitrite, inducible nitric oxide synthase, Kamebakaurin